Some Properties of Fuzzy Anti-Inner Product Spaces - Ali, Radhi I. M.; Hussein, Esraa A. (Iraqi Journal of Science, 2020)
In this paper, the definition of fuzzy anti-inner product in a linear space is introduced. Some results of fuzzy anti-inner product spaces are given, such as the relation between fuzzy inner product space and fuzzy anti-inner product. The notion of minimizing vector is introduced in fuzzy anti-inner product settings.